PENEGAKAN HUKUM TERHADAP PELAKU PERDAGANGAN HEWAN BELANGKAS BERDASARKAN UNDANG –UNDANG NOMOR 5 TAHUN 1990 TENTANG KONSERVASI SUMBER DAYA ALAM HAYATI DAN EKOSISTEMNYA DI KABUPATEN ROKAN HILIR - Hasbillah, Rahmat; Lestari, Maria Maya; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Irresponsible actions against the trade in belangkas animals can cause damage to natural reserves and natural sustainability areas as well as actions that violate the provisions on the protection of plants and animals covered, in the form of severe criminal penalties and fines. The severe criminal is seen as necessary because the damage to the resilience of one element of biological natural resources and ecosystems will result in great losses for communities that cannot be valued materially, while recovery in the original state is no longer possible. The purpose of writing this thesis, namely: First, to find out how the law enforcement process against the perpetrators of the belangkas animal trade based on Law No. 5 of 1990 concerning the Conservation of Biological Natural Resources and Ecosystems in Rokan Hilir, Second, to find out how prevention efforts are carried out by the Police and conservation centers against belangkas animal traffickers.This type of research is sociological juridical research, because in research the author directly conducts research on the location or place of research to provide a complete and clear picture of the problem studied. Rokan Hilir research location, Rokan Hilir Police, DITPOLAIRUD Riau Police, and Natural Resources Conservation Center (BKSDA) riau province. Data sources are used, primary data, secondary data, and tertier data. Data collection techniques in this study are interview techniques, literature studies, and data analysis. From the results of the problem research there are two main things that can be concluded. First, in the law enforcement process in the case of the sale of horseshoecrabanimals in Rokan Hilir coordination between the BKSDA and the Riau Provincial Police, has been running. From the level of investigation, the search for evidence, the arrest of suspects, to the investigation although there are still violations by buying the horseshoecrab.Keyword: Law Enforcement- Horseshoecrab- Rokan Hilir